High-viscosity cold-mixed and cold-laid fine thin overlay asphalt concrete and preparation method thereof
By adding modifiers such as SBS, vinyl trimethoxysilane and polyethylene-polypropylene copolymer to the cold mixing asphalt mixture, high viscosity cold mixing and cold-paved thin surface asphalt concrete is prepared, and the existing cold mixing is solved. The problem of insufficient bonding effect and anti-aging performance of asphalt mixtures has achieved better bonding, anti-aging performance and service life.
Patent Information
- Application Number
- CN202411301973.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-07
AI Technical Summary
The existing cold-mixed asphalt mixture has shortcomings in terms of bonding effect and anti-aging properties, which leads to easy shedding and short service life, making it difficult to meet construction needs.
Use high-viscosity cold-mixed and cold-paved thin surface asphalt concrete to improve the asphalt by adding SBS, vinyl trimethoxysilane and polyethylene-polypropylene copolymer to the matrix asphalt, modifying elastomers and zeolite powder and other raw materials to improve the asphalt Viscosity, flexibility and bonding.
It significantly improves the adhesion between the asphalt and the original pavement, extends the service life of the pavement, enhances anti-aging performance and toughness, and meets the technical needs of construction.
Smart Images

Figure BDA0005047917220000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of asphalt, and more specifically, to a high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete and a preparation method thereof. Background Art
[0002] In the process of continuous development of highway construction, the maintenance of highway asphalt pavement has received more and more attention and importance. The planning of highway network and the urgent need for maintenance of asphalt pavement indicate that my country has entered an era of equal emphasis on highway construction and maintenance. In order to maintain the good service status of the pavement, reduce the occurrence of pavement diseases, delay the development of early diseases, extend the service life of the pavement, and reduce the maintenance cost, it is of great significance to the sustainable development of highways themselves and the social economy to reasonably select the maintenance time and maintenance technology according to the changes in the performance of asphalt pavement and implement preventive pavement maintenance.
[0003] There are many types of preventive maintenance technologies for asphalt pavements, and there are different maintenance methods and technologies for different types of pavement diseases. At present, hot-mix asphalt mixtures are mostly used for pavement construction and maintenance. The hot-mix asphalt mixture is laid on the pavement, which has high requirements for construction conditions and cannot be opened to traffic immediately after construction. Although cold-mix asphalt mixtures are laid on the pavement, they have the advantages of energy saving, environmental protection and easy construction, but the current cold-mix asphalt has poor bonding effect with the original pavement, is easy to fall off, has poor anti-aging performance, and has a short service life, which is difficult to meet construction needs. Summary of the invention
[0004] In order to solve the above problems, the present application provides a high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete and a preparation method thereof.
[0005] In the first aspect, the present application provides a high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete, which adopts the following technical solution: A high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete comprises the following raw materials in parts by weight: 80-90 parts of base asphalt, 13-15 parts of polyethylene-polypropylene copolymer, 5-8 parts of modified elastomer, 0.1-0.2 parts of asphalt stabilizer, 3-5 parts of water-based epoxy resin, 0.3-0.5 parts of plasticizer, 2-2.5 parts of anti-aging agent and 600-650 parts of aggregate; The matrix asphalt comprises the following preparation steps: S1: 90-100 parts by weight of petroleum asphalt is swollen at 170-175° C. for 1-2 hours, the petroleum asphalt is fully ground at a temperature of 170-175° C., and then 5-8 parts by weight of SBS, 0.05-0.08 parts by weight of vinyl trimethoxy silane, 13-15 parts of polyethylene-polypropylene copolymer and 5-8 parts by weight of rubber softening oil are added to obtain a mixture; S2: Stir the above mixture evenly at a temperature of 175-180°C, then add 2-3 parts by weight of emulsifier and 30-32 parts by weight of water and stir thoroughly to obtain base asphalt.
[0006] By adopting the above technical scheme, SBS is added to the petroleum asphalt in the present application. When SBS is dispersed in the petroleum asphalt, the colloidal structure balance in the original petroleum asphalt is destroyed, SBS absorbs aromatic hydrocarbons and colloids in the petroleum asphalt, and swells to establish a new colloidal structure system, so that the modified asphalt maintains good flexibility and high viscosity, thereby improving the adhesion with the original pavement and comprehensively improving the performance of the petroleum asphalt; Petroleum asphalt and SBS are prone to segregation. The present application also adopts vinyl trimethoxy silane to improve the compatibility of petroleum asphalt and SBS. Vinyl trimethoxy silane contains silicone, which can also increase the viscosity of the base asphalt, further improving the bonding between the base asphalt and the original pavement; the polyethylene-polypropylene copolymer in the present application can effectively improve the comprehensive performance of the cold-mix asphalt mixture and extend the service life of the pavement, and due to the action of vinyl trimethoxy silane, the polyethylene-polypropylene copolymer is evenly and stably dispersed in the base asphalt, avoiding the occurrence of segregation.
[0007] Preferably, the modified elastomer comprises the following preparation steps: 20-22 parts by weight of polyether polyol, 25-35 parts by weight of diphenylmethane diisocyanate, 22-24 parts by weight of polytetrahydrofuran diol and 3-7 parts by weight of zeolite powder are uniformly mixed, reacted at 70-85° C. for 50-100 minutes, and granulated to obtain a modified elastomer.
[0008] By adopting the above technical scheme, the elastic particles prepared by the above preparation method in the present application have good elasticity and can effectively improve the flexibility of the road surface. The present application also incorporates zeolite powder into the elastic particles. When the elastic particles are directly impacted by the outside world, they can be buffered by the elastic displacement and resetting of the zeolite powder, thereby improving the elastic effect of the elastomer. In addition, the zeolite has rich pores, and the matrix asphalt can penetrate into the zeolite. The zeolite forms an anchor point, which increases the bonding force between the elastomer and the matrix asphalt and enhances the stability of the elastomer.
[0009] Preferably, the particle size of the modified elastomer is 1-4 mm.
[0010] By adopting the above technical solution, when the particle size of the modified elastomer is 1-4 mm, the asphalt pavement has good flexibility and strong bonding performance with asphalt, thereby improving the toughness and stability of the asphalt pavement.
[0011] Preferably, the asphalt stabilizer includes montmorillonite and hydroxymethyl cellulose.
[0012] By adopting the above technical scheme, hydroxymethyl cellulose is a high molecular polymer with good thickening properties. In asphalt mixture, cellulose ether can increase the viscosity of asphalt and improve its structural stability. Montmorillonite is a layered silicate mineral with a large specific surface area and good adsorption properties. In asphalt mixture, montmorillonite can adsorb oil in asphalt to form a stable asphalt-montmorillonite intercalation complex, which can limit the sedimentation of asphalt and avoid stratification. The combined use of montmorillonite and hydroxymethyl cellulose can effectively improve the stability of asphalt.
[0013] Preferably, the mass ratio of the montmorillonite to the hydroxymethyl cellulose is 1:1.
[0014] By adopting the above technical solution, when the mass ratio of montmorillonite to hydroxymethyl cellulose is 1:1, the performance of the prepared asphalt is relatively stable.
[0015] Preferably, the plasticizer is dioctyl phthalate.
[0016] By adopting the above technical solution, dioctyl phthalate can reduce the glass transition temperature of asphalt, improve its flexibility, make asphalt less prone to brittle cracking at low temperatures, and improve the durability of the road. Dioctyl phthalate can also improve the plasticity of asphalt, making it easier to spread and compact during construction, thereby improving construction efficiency.
[0017] Preferably, the anti-aging agent is paraffin.
[0018] By adopting the above technical solution, paraffin has a suitable carbon distribution, normal isomer ratio and migration speed, forming a dense protective film on the asphalt surface to prevent ozone aging and extend the service life of asphalt.
[0019] In the second aspect, the present application provides a method for preparing high-viscosity cold-mixed cold-laid fine thin overlay asphalt concrete, which adopts the following technical solution: S1: fully stirring the base asphalt, asphalt stabilizer, waterborne epoxy resin, plasticizer and anti-aging agent at 170-195°C to obtain a mixed solution; S2: Add the aggregate and modified elastomer into the mixed liquid, mix evenly, and obtain high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete.
[0020] By adopting the above technical solution, the preparation method of the present application has simple steps, is easy to operate, and is suitable for large-scale industrial production.
[0021] In summary, this application has the following beneficial effects: 1. The base asphalt in this application adopts SBS modified petroleum asphalt, so that the modified asphalt maintains good flexibility and high viscosity, thereby improving the adhesion with the original road surface, comprehensively improving the performance of petroleum asphalt, and improving the anti-aging and noise reduction performance of asphalt; Petroleum asphalt and SBS are prone to segregation, and this application also adopts vinyl trimethoxy silane to improve the compatibility of petroleum asphalt and SBS. Vinyl trimethoxy silane contains silicone, which can also increase the viscosity of the base asphalt, further improving the bonding between the base asphalt and the original road surface.
[0022] 2. The elastic particles prepared by the above-mentioned preparation method in the present application have good elasticity and can effectively improve the flexibility of the road surface. The present application also incorporates zeolite powder into the elastic particles. When the elastic particles are directly impacted by the outside world, they can be buffered by the elastic displacement and resetting of the zeolite powder, thereby improving the elastic effect of the elastomer. In addition, the zeolite has rich pores, and the matrix asphalt can penetrate into the zeolite. The zeolite forms an anchor point, which increases the bonding force between the elastomer and the matrix asphalt and enhances the stability of the elastomer.
[0023] Source of raw materials SBS comes from Borida New Materials Co., Ltd., brand name YH-792E; Vinyltrimethoxysilane was from Jining Hongming Chemical Reagent Co., Ltd., model 02; The rubber softening oil is aromatic oil, which comes from Shandong Xinglong New Materials Co., Ltd.; The emulsifier was from Jinan Youshengyuan Chemical, model OP-10; Isopropyl triisostearyl titanate was from Zhongshan Dixin Chemical Co., Ltd., model number wang2; Polyether polyol was from Jining Hongming Chemical Reagent Co., Ltd., model 403; Diphenylmethane diisocyanate was from Hubei Xinrunde Chemical Co., Ltd.; Polytetrahydrofurandiol was obtained from Guangdong Wengjiang Chemical Reagent Co., Ltd., product number PTMEG; Zeolite powder comes from Hongchang Mineral Products Processing Plant in Lingshou County, with a particle size of 20-50 μm; Polyethylene-polypropylene copolymer was from Shanghai Fengxin New Material Technology Co., Ltd., brand 6202; Montmorillonite was from Yanguo Mineral Products Processing Plant in Lingshou County, model MT101; Waterborne epoxy resin was from Nanjing Serunde New Material Technology Co., Ltd., brand E-20; Dioctyl phthalate was from Shandong Shunchang New Material Technology Co., Ltd., item number 001; Paraffin wax is microcrystalline wax from Fushun Junding Chemical Co., Ltd. Hydroxymethylcellulose was from Jinan Zhendong Chemical Co., Ltd., item number 2026. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with preparation examples and embodiments.
[0025] Preparation Example Preparation of base asphalt Preparation Example 1.1 The base asphalt comprises the following preparation steps: S1: 90 kg of No. 90 petroleum asphalt was swelled at 170° C. for 1 h, the No. 90 petroleum asphalt was fully ground at 170° C., and then 5 kg of SBS, 0.05 kg of vinyl trimethoxysilane, 13 kg of polyethylene-polypropylene copolymer and 5 kg of rubber softening oil were added to obtain a mixture; S2: Stir the above mixture evenly at a temperature of 175°C, then add 2kg of emulsifier and 30kg of water, stir thoroughly to obtain base asphalt.
[0026] Preparation Example 1.2 The base asphalt comprises the following preparation steps: S1: 95 kg of No. 90 petroleum asphalt was swelled at 172° C. for 1.5 h, the No. 90 petroleum asphalt was fully ground at 173° C., and then 7 kg of SBS, 0.06 kg of vinyl trimethoxysilane, 14 kg of polyethylene-polypropylene copolymer and 7 kg of rubber softening oil were added to obtain a mixture; S2: Stir the above mixture evenly at a temperature of 177°C, then add 2.5kg of emulsifier and 31kg of water, stir thoroughly, and obtain base asphalt.
[0027] Preparation Example 1.3 The base asphalt comprises the following preparation steps: S1: 100 kg of No. 90 petroleum asphalt was swelled at 175° C. for 2 h, the No. 90 petroleum asphalt was fully ground at 175° C., and then 8 kg of SBS, 0.08 kg of vinyl trimethoxysilane, 15 kg of polyethylene-polypropylene copolymer and 8 kg of rubber softening oil were added to obtain a mixture; S2: Stir the above mixture evenly at a temperature of 180°C, then add 3kg of emulsifier and 32kg of water, stir thoroughly to obtain base asphalt.
[0028] Preparation Example 1.4 The difference between Preparation Example 1.4 and Preparation Example 1.3 is that an equal amount of triisostearyl titanate isopropyl is used in step S1 to replace vinyl trimethoxy silane, and the remaining steps are the same as those of Preparation Example 1.3.
[0029] Preparation of modified elastomers Preparation Example 2.1 The modified elastomer comprises the following preparation steps: 20 kg of polyether polyol, 25 kg of diphenylmethane diisocyanate, 22 kg of polytetrahydrofuran diol and 3 kg of zeolite powder were mixed evenly, reacted at 70° C. for 50 minutes, and granulated to obtain a modified elastomer, wherein the particle size of the modified elastomer was 0.5-1 mm.
[0030] Preparation Example 2.2 The modified elastomer comprises the following preparation steps: 21 kg of polyether polyol, 30 kg of diphenylmethane diisocyanate, 23 kg of polytetrahydrofuran diol and 5 kg of zeolite powder were mixed evenly, reacted at 80° C. for 75 minutes, and granulated to obtain a modified elastomer, wherein the particle size of the modified elastomer was 0.5-1 mm.
[0031] Preparation Example 2.3 The modified elastomer comprises the following preparation steps: 22 kg of polyether polyol, 35 kg of diphenylmethane diisocyanate, 24 kg of polytetrahydrofuran diol and 7 kg of zeolite powder were mixed evenly, reacted at 85° C. for 100 minutes, and granulated to obtain a modified elastomer, wherein the particle size of the modified elastomer was 0.5-1 mm.
[0032] Preparation Example 2.4 The difference between Preparation Example 2.4 and Preparation Example 2.3 is that no zeolite powder is added, and the remaining steps are the same as Preparation Example 2.3.
[0033] Preparation Example 2.5 The difference between Preparation Example 2.5 and Preparation Example 2.3 is that the particle size of the modified elastomer obtained by granulation is 1-4 mm, and the remaining steps are the same as Preparation Example 2.3.
[0034] Preparation Example 2.6 The difference between Preparation Example 2.6 and Preparation Example 2.3 is that the particle size of the modified elastomer obtained by granulation is 4-10 mm, and the remaining steps are the same as Preparation Example 2.3. Example
[0035] Example 1 A method for preparing high-viscosity cold-mixed cold-laid fine thin overlay asphalt concrete comprises the following steps: S1: 80 kg of base asphalt (from Preparation Example 1.1) was heated to 170°C, 0.1 kg of asphalt stabilizer (montmorillonite), 3 kg of waterborne epoxy resin, 0.3 kg of plasticizer (dioctyl phthalate) and 2 kg of anti-aging agent (paraffin) were added in sequence, and stirred at a speed of 200 r / min for 15 min to obtain a mixed solution; S2: Add 600 kg of aggregate and 5 kg of modified elastomer (from Preparation Example 2.1) into the mixed liquid, stir at a speed of 500 r / min for 30 min to obtain high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete; wherein the aggregate is basalt with a particle size of 0.7-1 cm.
[0036] Example 2 A method for preparing high-viscosity cold-mixed cold-laid fine thin overlay asphalt concrete comprises the following steps: S1: 85 kg of base asphalt (from Preparation Example 1.2) was heated to 180°C, 0.15 kg of asphalt stabilizer (montmorillonite), 4 kg of waterborne epoxy resin, 0.4 kg of plasticizer (dioctyl phthalate) and 2.2 kg of anti-aging agent (paraffin) were added in sequence, and stirred at a speed of 200 r / min for 15 min to obtain a mixed solution; S2: Add 620 kg of aggregate and 7 kg of modified elastomer (from Preparation Example 2.2) into the mixed liquid, stir at a speed of 500 r / min for 30 min to obtain high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete; wherein the aggregate is basalt with a particle size of 0.7-1 cm.
[0037] Example 3 A method for preparing high-viscosity cold-mixed cold-laid fine thin overlay asphalt concrete comprises the following steps: S1: 90 kg of base asphalt (from Preparation Example 1.3) was heated to 195°C, 0.2 kg of asphalt stabilizer (montmorillonite), 5 kg of waterborne epoxy resin, 0.5 kg of plasticizer (dioctyl phthalate) and 2.5 kg of anti-aging agent (paraffin) were added in sequence, and stirred at a speed of 200 r / min for 15 min to obtain a mixed solution; S2: Add 650 kg of aggregate and 8 kg of modified elastomer (from Preparation Example 2.3) into the mixed liquid, stir at a speed of 500 r / min for 35 minutes to obtain high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete; wherein the aggregate is basalt with a particle size of 0.7-1 cm.
[0038] Example 4 The difference between Example 4 and Example 3 is that the base asphalt comes from Preparation Example 1.4, and the remaining steps are the same as Example 3.
[0039] Example 5 The difference between Example 5 and Example 3 is that the modified elastomer comes from Preparation Example 2.4, and the remaining steps are the same as Example 3.
[0040] Example 6 The difference between Example 6 and Example 3 is that the modified elastomer comes from Preparation Example 2.5, and the remaining steps are the same as Example 3.
[0041] Example 7 The difference between Example 7 and Example 3 is that the modified elastomer comes from Preparation Example 2.6, and the remaining steps are the same as Example 3.
[0042] Example 8 The difference between Example 8 and Example 6 is that the asphalt stabilizer includes 0.1 kg montmorillonite and 0.1 kg hydroxymethyl cellulose, the mass ratio of montmorillonite to hydroxymethyl cellulose is 1:1, and the remaining steps are the same as those in Example 6.
[0043] Example 9 The difference between Example 9 and Example 6 is that the asphalt stabilizer includes 0.12 kg montmorillonite and 0.08 kg hydroxymethyl cellulose, the mass ratio of montmorillonite to hydroxymethyl cellulose is 1.5:1, and the remaining steps are the same as those in Example 6.
[0044] Example 10 The difference between Example 10 and Example 6 is that the asphalt stabilizer includes 0.08 kg montmorillonite and 0.12 kg hydroxymethyl cellulose, the mass ratio of montmorillonite to hydroxymethyl cellulose is 1:1.5, and the remaining steps are the same as in Example 6.
[0045] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the base asphalt is No. 90 petroleum asphalt, and the remaining preparation steps are the same as those of Example 1.
[0046] Comparative Example 2 The difference between Comparative Example 1 and Example 1 is that polyethylene-polypropylene copolymer is not added to the base asphalt, and the remaining preparation steps are the same as those of Example 1.
[0047] Performance testing Detection Methods The ductility, softening point, viscosity, toughness and stability of the asphalt concrete prepared in Examples 1-10 and Comparative Examples 1-2 were tested according to DG / TJ08-2074-2010 standard; Anti-aging test: The asphalt concrete samples with a specification of 5cm×5cm×2cm prepared in Examples 1-10 and Comparative Examples 1-2 were placed in an ultraviolet oven for accelerated aging test. The ultraviolet light intensity was 50uw / cm2, the temperature was 40°C, and the test time was 7 days. The shedding of aggregates and elastomers in the asphalt concrete was observed.
[0048] The specific data are shown in the following table: Table 1 Comprehensive performance of asphalt concrete prepared in Examples 1-10 and Comparative Examples 1-2 Combining the data of Examples 1-3 and Table 1, it can be seen that the asphalt concrete prepared in the present application has an elongation of more than 55 cm at 15°C, a softening point of 90°C, a dynamic viscosity of 159200 Pa·s at 60°C, and a toughness of 36 N·m. After the anti-aging performance test, no particles fell off. Therefore, the asphalt concrete prepared in the present application has good plasticity, high-temperature deformation resistance, adhesion and anti-aging performance.
[0049] Combining the data of Examples 3-4 and Table 1, it can be seen that the vinyl trimethoxysilane in the present application can improve the compatibility of petroleum asphalt and SBS, thereby improving the comprehensive performance of asphalt concrete; Combining the data of Example 3, Example 5 and Table 1, it can be seen that adding zeolite to the elastomer can better improve the deformation resistance and toughness of asphalt concrete.
[0050] Combining the data of Example 3, Examples 6-7 and Table 1, it can be seen that when the particle size of the modified elastomer is 1-4 mm, the asphalt pavement has good flexibility. Although the increase in the particle size of the elastomer is beneficial to increasing the toughness of the asphalt pavement, considering that the larger the particle size of the modified elastomer, the easier it is to fall off and to a certain extent affect the compressive strength of the pavement, the particle size of the modified elastomer is preferably 1-4 mm.
[0051] Combining the data of Example 6, Examples 8-10 and Table 1, it can be seen that the combined use of montmorillonite and hydroxymethyl cellulose can effectively improve the stability of asphalt, thereby improving the comprehensive performance of asphalt. When the mass ratio of montmorillonite to hydroxymethyl cellulose is 1:1, the performance of the prepared asphalt is better.
[0052] Combining the data of Example 1, Comparative Example 1 and Table 1, it can be seen that the base asphalt prepared in the present application has good plasticity, high temperature deformation resistance, adhesion and anti-aging properties.
[0053] Combining the data of Example 1, Comparative Example 2 and Table 1, it can be seen that the polyethylene-polypropylene copolymer in the present application can effectively improve the comprehensive performance of asphalt.
[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete, characterized by: The invention comprises the following raw materials in parts by weight: 80-90 parts of base asphalt, 5-8 parts of modified elastomer, 0.1-0.2 parts of asphalt stabilizer, 3-5 parts of waterborne epoxy resin, 0.3-0.5 parts of plasticizer, 2-2.5 parts of anti-aging agent and 600-650 parts of aggregate; The matrix asphalt comprises the following preparation steps: S1: 90-100 parts by weight of petroleum asphalt is swollen at 170-175° C. for 1-2 hours, the petroleum asphalt is fully ground at a temperature of 170-175° C., and then 5-8 parts by weight of SBS, 0.05-0.08 parts by weight of vinyl trimethoxy silane, 13-15 parts of polyethylene-polypropylene copolymer and 5-8 parts by weight of rubber softening oil are added to obtain a mixture; S2: Stir the above mixture evenly at a temperature of 175-180°C, then add 2-3 parts by weight of emulsifier and 30-32 parts of water, stir well to obtain base asphalt.
2. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 1, characterized in that: The modified elastomer comprises the following preparation steps: 20-22 parts by weight of polyether polyol, 25-35 parts by weight of diphenylmethane diisocyanate, 2224 parts by weight of polytetrahydrofuran diol and 3-7 parts by weight of zeolite powder are uniformly mixed, reacted at 70-85° C. for 50-100 min, and granulated to obtain a modified elastomer.
3. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 2, characterized in that: The particle size of the modified elastomer is 1-4 mm.
4. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 1, characterized in that: The asphalt stabilizer includes montmorillonite and hydroxymethyl cellulose.
5. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 4, characterized in that: The mass ratio of the montmorillonite to the hydroxymethyl cellulose is 1:
1.
6. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 1, characterized in that: The plasticizer is dioctyl phthalate.
7. The high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete according to claim 1, characterized in that: The anti-aging agent is paraffin.
8. A high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete as described in claims 1-7, characterized in that: The method comprises the following preparation steps: S1: fully stirring the base asphalt, asphalt stabilizer, waterborne epoxy resin, plasticizer and anti-aging agent at 170-195°C to obtain a mixed solution; S2: Add the aggregate and modified elastomer into the mixed liquid, mix evenly, and obtain high-viscosity cold-mixed cold-laid fine thin-surface asphalt concrete.